Lexical-Semantic and Phonological Processing Deficits in Wernicke’s Aphasia - Burcu Aydın (Dilbilim Araştırmaları Dergisi)
This study investigates the lexical-semantic and phonological processing deficits in Wernicke’s aphasia by comparing with healthy controls aiming to shed light on the causes of impairment. Identifying and Picture-Naming, Lexical-Semantic Association and Rhyme Recognition Tests were used to assess the processing. The results showed that Wernicke’s aphasics have the inability to retrieve a name associated with a picture but they were able to match the semantic prime with the associated target image similar to the control group. The results revealed that Wernicke’s aphasics are capable of dealing with lexical-semantic processing and semantic judgment. Rhyme Recognition Test results revealed that Wernicke aphasics have partially preserved comprehension of printed language. The results of this study also showed that Wernicke’s aphasics performed significantly lower accuracy than controls on the phonological test and performed comparably on the semantic test. It is concluded that their deficits are likely to be related to access to the phonological representations of words.